American Lutheran arguments about slavery. Issue 2 (30th March 2021) - Erling, Maria
Abstract: 19th century Lutherans in the United States confronted the presence of slavery not only as a social condition but as a theological challenge. Immigrants who formed Lutheran churches and gathered into synods also had to choose alliances among the Lutheran groups already present. Most traditional histories of this process of denominational formation focus on the confessional standpoints of the various groups, but underneath and hovering over these discussions of theology and doctrine were positions on antislavery movements and the coming of the Civil War. These social realities affected the theological formation of Lutheranism in the United States.